Biologically consistent dose accumulation using daily patient imaging - Niebuhr, Nina Isabelle; Splinter, Mona; Bostel, Tilman; Seco, Joao; Hentschke, Clemens M.; Floca, Ralf; Hörner-Rieber, Juliane; Alber, Markus; Huber, Peter E.; Nicolay, Nils; Pfaffenberger, Asja (Radiation oncology, 2021)
This work addresses a basic inconsistency in the way dose is accumulated in radiotherapy when predicting the biological effect based on the linear quadratic model (LQM). To overcome this inconsistency, we introduce and evaluate the concept of the total biological dose, bEQDd.
Gesehen am 04.06.2021